ความชุกของปัญหาพฤติกรรมและปัจจัยที่เกี่ยวข้องกับพฤติกรรมของนักเรียนชั้นมัธยมศึกษาปีที่ 2 จังหวัดสมุทรสงคราม - วรรณวิไล กมลกิจวัฒนา (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purpose of this cross-sectional survey were to study the prevalence rate of behavioral problems and their related factors among Mathayom II students in Samutsongkhram Province during 2544 BE academic year. Data were collected for 420 students by means of 5 sets of self-administered questionnaires : Personal Data, Emotional Questionnaire and the Strength Difficulties Questionnaire (SDQ) answered by the student and ; the two sets of another Strength Difficulties Questionnaire (SDQ), each answered by the teacher and the student s parent. The results showed that the prevalence rates of behavioral problems among these students were 17.3 percent for emotional problems, 19.2 percent for conduct disorder, 20.6 percent for attention deficit hyperactivity disorder and 17.0 percent for peer relationship problem (46.4 percent overall). Approximately 22.2 percent of the students had more than one problem. Factors significantly related to these problems included sex, relationship with siblings, emotional quotient, parent s career, type of school and the way of student treatment by the teacher. It is thus necessity for the school administrators, teachers and parents to act cooperatively in identifying and helping students with behavioral problems.